?MICROBIAL PRODUCTION OF XYLITOL FROM ACID TREATED CORN COBS (Biological Sciences - PJSIR, 2003)
The fermentation of xylan hydrolyzate corn cobs by different yeast species revealed the formation of different polyalcohol sugars. Both Schizosaccharomyces japonicus and Kluyveromyces bulgaricus form xylitol as sole product. Relatively high xylitol pro-duction by S. japonicus and K. bulgaricus was achieved under static fermentation, among other parameters, initial pH 9 and 8, carbon concentrations 88 - 110 g / l, ammonium chloride 1.0, 2.0 g / l and 10, 15 g / l yeast extract for S. janponicus and K. bulgricus, respectively were obtained. However, maximal xylitol yields were recorded after 4 days of incubation for S. japonicus (18 g / l) and K. bulgaricus (16 g / l), respectively.